Pengaruh Latihan Dribble Zig-Zag terhadap Peningkatan Kecepatan Dribbling Pemain Sepak Bola U-14 di SSB Selection FC Pabuaran - Ahmad Rangga Prihadit; Didi Muhtarom (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Football is a sport that requires mastery of basic techniques, one of which is dribbling. Dribbling techniques are very important because they serve to control the ball, pass opponents, and create opportunities in the game. Based on initial observations at SSB Selection FC Pabuaran, Cirebon Regency, it is known that the mastery of dribbling techniques in U-14 athletes is still relatively low. This is shown through unfocused gaze when dribbling, improper touching, and lack of balance when dribble, which has an impact on the effectiveness of the game and the team's overall performance. One of the factors that causes the weakness of dribbling ability is the lack of variety of exercises, especially those that emphasize the aspects of speed and agility. Exercises with the zig-zag trajectory method are an effective form of exercise to improve speed, agility, and ball control. This method helps hone motor response, maneuver accuracy, and dribbling skills in dynamic game conditions. This study aims to find out the extent of the influence of dribbling practice using the zig-zag trajectory method on increasing dribbling speed in U-14 football athletes at SSB Selection FC Pabuaran. The research uses a quantitative approach with experimental methods. Data collection techniques were carried out through observation and dribbling tests before and after treatment. The results of this study are expected to provide an empirical picture of the effectiveness of zig-zag training on the technical aspects of the game of football at an early age. In addition, this research is also expected to be a reference for coaches in designing a more structured training program that is in accordance with the development needs of young athletes. Thus, the development of basic techniques from an early age will be more optimal and contribute to the improvement of national football achievements in the future.